Numerical and experimental analysis of natural convection in a cavity heated from below - Ramos, RAV; Milanez, L. F. (Taylor & Francis Ltd, 1998)
In this work, an analysis of the natural convection flow caused by heat sources dissipating energy at a constant rate simulating electronic components mounted at the bottom surface of a cavity symmetrically cooled from the sides and insulated at the top is performed. This problem was studied numerically and experimentally for several aspect ratios (height/width), for different levels of dissipation in the sources, and for different side wall temperatures. Temperature and velocity fields were determined as well as the temperature variation along the surface where the sources are mounted and the average Nusselt number in the source surfaces. Numerical and experimental results were found to agree.